Pharmacovigilance pregnancy data in a large population of patients with chronic inflammatory disease exposed to certolizumab pegol. (April 2022) - Clowse, Megan; Fischer-Betz, Rebecca; Nelson-Piercy, Catherine; Scheuerle, Angela E.; Stephan, Brigitte; Dubinsky, Marla; Kumke, Thomas; Kasliwal, Rachna; Lauwerys, Bernard; Förger, Frauke
Introduction: Chronic inflammatory diseases (CIDs), including rheumatic diseases and other inflammatory conditions, often affect women of reproductive age. Tumor necrosis factor inhibitors (TNFi) are widely used to treat CID, but there is limited information on outcomes of TNFi-exposed pregnancies. We evaluated pregnancy outcomes from 1392 prospectively reported pregnancies exposed to certolizumab pegol (CZP), a PEGylated, Fc-free TNFi with no to minimal placental transfer. Methods: CZP-exposed pregnancies in patients with CID from the UCB Pharmacovigilance global safety database were reviewed from the start of CZP clinical development (July 2001) to 1 November 2020. To limit bias, the analysis focused on prospectively reported cases with known pregnancy outcomes. Results: In total, 1392 prospective pregnancies with maternal CZP exposure and known pregnancy outcomes ( n  = 1425) were reported; 1021 had at least first-trimester CZP exposure. Live birth was reported in 1259/1425 (88.4%) of all prospective outcomes. There were 150/1425 (10.5%) pregnancy losses before 20 weeks (miscarriage/induced abortion), 11/1425 (0.8%) stillbirths, and 5/1392 (0.4%) ectopic pregnancies. Congenital malformations were present in 30/1259 (2.4%) live-born infants, of which 26 (2.1%) were considered major according to the Metropolitan Atlanta Congenital Defects Program criteria. There was no pattern of congenital malformations. Discussion and conclusion: No signal for adverse pregnancy outcomes or congenital malformations was observed in CZP-exposed pregnancies. Although the limitations of data collected through this methodology (including underreporting, missing information, and absence of a comparator group) should be considered, these data provide reassurance for women with CID who require CZP treatment during pregnancy, and their treating physicians.